2018
DOI: 10.1111/jcmm.13595
|View full text |Cite
|
Sign up to set email alerts
|

INPP4B restrains cell proliferation and metastasis via regulation of the PI3K/AKT/SGK pathway

Abstract: Cervical cancer continues to be among the most frequent gynaecologic cancers worldwide. The phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT) pathway is constitutively activated in cervical cancer. Inositol polyphosphate 4‐phosphatase type II (INPP4B) is a phosphoinositide phosphatase and considered a negative regulatory factor of the PI3K/AKT pathway. INPP4B has diverse roles in various tumours, but its role in cervical cancer is largely unknown. In this study, we investigated the role of INPP4B in cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Thus, up-regulation of the expression of these multifunctional kinases (SGK1 and SGK3) in glioma cells under glucose deprivation conforms well to pro-proliferative role of these proteins. At the same time, inhibition of ERN1 signaling enzyme function has strong but different effect on their expression indicating ERN1 dependent character of these gene expressions and variable role in ERN1 signaling (Chen et al 2018;Li et al 2018b;Cao et al 2019;Fan et al 2019;Ma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, up-regulation of the expression of these multifunctional kinases (SGK1 and SGK3) in glioma cells under glucose deprivation conforms well to pro-proliferative role of these proteins. At the same time, inhibition of ERN1 signaling enzyme function has strong but different effect on their expression indicating ERN1 dependent character of these gene expressions and variable role in ERN1 signaling (Chen et al 2018;Li et al 2018b;Cao et al 2019;Fan et al 2019;Ma et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…7 The INPP4B gene harbors a series of special structures, such as a C2 lipid binding domain at the N-terminal that promotes the dephosphorylation and degradation of phosphatidylinositol-3,4 diphosphate, thereby inhibiting AKT activation, blocking PI3K/AKT signaling pathway transmission, and inhibiting tumor progression. 8 The PTEN gene, as the first cancer suppressor gene with bispecific phosphatase activity is widely expressed in normal tissues. 9 PTEN protein converts 3,4,5-phosphatidylinositol into 4,5-phosphatidylinositol, induces Caspase-9 protein expression, and mediates cancer cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since SGK3 was a target gene regulated by miR-335-5p, and it was shown to affect the cell proliferation in many types of cells (Sun et al 2016, Chen et al 2018, we hypothesized that miR-335-5p might be associated with the growth and proliferation in granulosa cells. assay revealed that the miR-335-5p mimics significantly decreased cell proliferation, whereas the miR-335-5p inhibitor promoted the proliferation of KGN cells ( Fig.…”
Section: Mir-335-5p Inhibited Kgn Cells Proliferationmentioning
confidence: 99%